Rate of venous thromboembolism and atrial fibrillation in a real-world case series of advanced cancer patients: the CaTEV Study. Issue 6 (June 2021) - Gurizzan, Cristina; Roca, Elisa; Faggiano, Andrea; Paoli, Dalila; Dinatolo, Elisabetta; Masini, Gabriele; Tomasi, Cesare; De Palma, Giuseppe; Metra, Marco; Berruti, Alfredo; Faggiano, Pompilio
Abstract : Background: Venous thromboembolism is the second leading cause of death in cancer patients and its incidence seems underestimated. In addition, cancer patients have an increased risk of developing atrial fibrillation, which may be the first presentation of cancer itself. The primary aim of this study was to define the incidence of venous thromboembolism (VTE) and atrial fibrillation in a real-word series of advanced cancer patients. Methods: We performed a retrospective single-institution study on patients diagnosed with stage IV solid neoplasia at the outpatient clinic of the Medical Oncology Unit (Spedali Civili Brescia, Italy), from January to December 2018. Results: A total of 403 patients were enrolled, with a mean age at presentation of 63 years (range 18–85 years). A VTE was observed in 24% of cases, half of which occurred after diagnosis of metastatic neoplasia, with a median time of onset of 5.5 months (range 0–84). About 3% of patients developed atrial fibrillation after cancer diagnosis. In this patient series, no statistically significant differences were found when comparing Khorana and PROTECHT thromboembolic risk scores, both before and after the start of chemotherapy. Overall, about 25% of the patients received anticoagulant therapy; in most cases, the drug of choice was low-molecular-weight heparin (LMWH). Conclusion: This study showed for cancer patients a considerably higher incidence of VTE and a comparable incidence of atrial fibrillation than reported in literature. Validated thromboembolic risk scores appear to be poorly predictive, and LMWH remains the most widely used anticoagulant drug.